The law of maritime blockade : past, present, and future - Drew, Phillip (Oxford : Oxford University Press, 2018)
Sets out the law applicable to maritime blockades in armed conflict, testing the traditional rules of maritime blockade against the requirements of contemporary international humanitarian law. An important issue addressed is the legality of a blockade even if it results in mass starvation of the affected population.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 11, 2017).
Keywords: Maritime law; Blockade -- History; Law; Laws of specific jurisdictions & specific areas of law